Cocaine induces cell death and activates the transcription nuclear factor kappa-b in pc12 cells - Lepsch, Lucilia B.; Munhoz, Carolina D.; Kawamoto, Elisa M.; Yshii, Lidia M.; Lima, Larissa S.; Curi-Boaventura, Maria F.; Salgado, Thais M. L.; Curi, Rui; Planeta, Cleopatra da Silva [UNESP]; Scavone, Cristoforo (Biomed Central Ltd., 2009)
Cocaine is a worldwide used drug and its abuse is associated with physical, psychiatric and social problems. The mechanism by which cocaine causes neurological damage is very complex and involves several neurotransmitter systems. For example, cocaine increases extracellular levels of dopamine and free radicals, and modulates several transcription factors. NF-kappa B is a transcription factor that regulates gene expression involved in cellular death. Our aim was to investigate the toxicity and modulation of NF-kappa B activity by cocaine in PC 12 cells. Treatment with cocaine (1 mM) for 24 hours induced DNA fragmentation, cellular membrane rupture and reduction of mitochondrial activity. A decrease in Bcl-2 protein and mRNA levels, and an increase in caspase 3 activity and cleavage were also observed. In addition, cocaine (after 6 hours treatment) activated the p50/p65 subunit of NF-kappa B complex and the pretreatment of the cells with SCH 23390, a D1 receptor antagonist, attenuated the NF-kappa B activation. Inhibition of NF-kappa B activity by using PDTC and Sodium Salicilate increased cell death caused by cocaine. These results suggest that cocaine induces cell death (apoptosis and necrosis) and activates NF-kappa B in PC12 cells. This activation occurs, at least partially, due to activation of D1 receptors and seems to have an anti-apoptotic effect on these cells.